1979
DOI: 10.1172/jci109418
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of receptor affinity to the modulation of thyroid hormone nuclear receptor levels and growth hormone synthesis by L-triiodothyronine and iodothyronine analogues in cultured GH1 cells.

Abstract: A B S T R A C T We have previously demonstrated that L-triiodothyronine (L-T3) induces an increase in growth hormone synthesis and messenger RNA in cultured GH1 cells, a rat pituitary cell line. In addition to regulating the growth hormone response, L-T3 elicits a time-and dose-dependent reduction in the level of its nuclear receptor, which is a direct function of the occupancy of the receptor binding site. In this study we have compared the relative affinity of L-T3, triiodothyroacetic acid, D-triiodothyroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
33
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(36 citation statements)
references
References 49 publications
2
33
1
Order By: Relevance
“…These relative affinities have been found for receptor in rat brain, liver, and kidney, and for receptor in a variety of cultured cell lines derived from the rat and other species (3,42,44,45). Scatchard analysis of hormone binding to receptor demonstrates linear plots with no evidence for positive or negative cooperativity (46)(47)(48)(49).…”
Section: General Properties Ofthyroid Hormone Receptorsmentioning
confidence: 89%
See 2 more Smart Citations
“…These relative affinities have been found for receptor in rat brain, liver, and kidney, and for receptor in a variety of cultured cell lines derived from the rat and other species (3,42,44,45). Scatchard analysis of hormone binding to receptor demonstrates linear plots with no evidence for positive or negative cooperativity (46)(47)(48)(49).…”
Section: General Properties Ofthyroid Hormone Receptorsmentioning
confidence: 89%
“…Similar results have been observed with receptor obtained from rat liver nuclei. The affinity of receptors for L-T3, L-T4, and other iodothyronines parallels the iodothyronine biologic potency in cultured cells (42) and in intact animals (44). If the affinity for receptor and the biologic potency of L-T3 is assigned the value of 1, the values for several well-studied iodothyronines are: triiodothyroacetic acid (TRIAC) (…”
Section: General Properties Ofthyroid Hormone Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in euthyroid rats suggested that T4 constituted 10-15% of the endogenous iodothyronines specifically associated with thyroid nuclear receptors in liver and kidney (15) but was not detected in anterior pituitary (16,17). T4 was shown to have intrinsic biological activity by Samuels et al (18), who showed that T4 induced growth hormone (GH) production and thyroid nuclear receptor down-regulation in GH, cells in the absence ofappreciable conversion ofT4 to T3. More recently, others have shown that GH1 cells do generate appreciable amounts of T3 from T4 (19).…”
Section: Introductionmentioning
confidence: 99%
“…Although T4 affects biological activity in anterior pituitary by means ofT3(T4), these reports (16)(17)(18)(19) also suggest that the role of T4 itself in thyroid hormone action in anterior pituitary is not clearly defined. The issue is important for understanding both the action of thyroid hormones under physiologic conditions and during the alterations in plasma thyroid hormone concentrations that occur in patients with nonthyroidal disease.…”
Section: Introductionmentioning
confidence: 99%